ARCHEOLOGICAL SITES DISSEMINATION IN THE CENTERS OF ISLAM DIFFUSION IN RURAL AREA OF CENTRAL JAWA - Budi Sulistiono; Misri Muchsin (Journal Analytica Islamica, 2021)
The propagation and Islamic teaching dissemination in JavaIsland, which had gone long for periods of time, were solely struggled bymerchants or leaders and small groups of traders. Islam, in Java Island,however, tended to be powerless to force on its development through awar.The trace of Islam in Central Java seemed very interesting to berecorded, especially in some places which were geographically located inrural area of Central Java. The data were mostly obtained from textual data.One of the subjects was Babad Tanah Jawi/the History of Java Island (sastrababad/ literature of history). The word babad means classic, story, history.Babad was considered as “history,” since it told about people in the past orancestry. Babad Tanah Jawi as one type of Java literature had mentioned thenames of figures and places showed a relationship with Islam spread in JavaIsland, especially in the Southern part of Central Java, located in the East ofGunung Merapi. From the tentative studies, there were several names ofplaces which were located in topographic maps. Coincidentally the namesof places which were mentioned in Babad Tanah Jawi had been investigatedas the R.O.D. inventory. In 1914-1915 there had been measurement to findout possibility of toponyms contained of archeological data during thediffusion of Islam. Basically the names which had been mentioned in BabadTanah Jawi probably had relationship with data of archeology, includingoral history in old people mind in the field of research